Challenges of Student Mobility in Southeast Asia - Do, Thu T; Pham, Duy N. (International Higher Education, 2016)
Southeast Asia has experienced a remarkable development of student mobility: A significantly increasing number of Southeast Asian students study abroad in western developed countries, and a gradually increasing number of international students from Southeast Asia, South Korea, China, India, and some western countries study in Southeast Asia. However, these countries also encounter several challenges to advancing these programs.